The Relationship Between Self-Efficacy and Elementary School Students' Mathematics Learning Outcomes - Urifah, Firda Nur; Fitrasari, Nisfi Laila; Farhan, Muhammad Fariza (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3617, 2025)
The purpose of this study was to examine the relationship between students' self-efficacy and their mathematics learning outcomes in elementary school. Perceived self-efficacy is very important for academic success, as it reflects students' confidence in their ability to understand and solve mathematical problems. This quantitative correlational study was conducted with 34 students from grades four to six. The Morgan-Jinks Student Self-Efficacy Scale was used, and daily mathematics assessment results were used as information related to achievement. Data analysis was performed using Spearman's rank correlation coefficient (rho) with SPSS version 25. The data revealed that the average self-efficacy score of students was 15.01 (standard deviation: 2.12), while the average mathematics score was 86.88 (standard deviation: 10.56). Correlation analysis revealed a coefficient of r of 0.401 and a p-value of 0.019, highlighting a positive and significant relationship between self-efficacy and mathematics performance. This observation shows that students with higher self-efficacy achieve better learning outcomes. This study underscores the need to develop self-efficacy through pedagogical approaches that foster students' confidence, engagement, and active participation in mathematics learning activities.